CLINICAL AND IMMUNOLOGICAL FEATURES OF BRONCHIAL ASTHMA ACCOMPANIED BY THYROID GLAND DISORDERS - I. A. Kamaeva; N. L. Shaporova; I. M. Gaiduk (Медицинская иммунология)
To reveal clinical and immunological features of bronchial asthma (BA) combined with thyroid gland pathology,  sixty patients have been examined  in  five equal groups, i.e., BA; hypothyroidism;  thyrotoxicosis; BA + hypothyroidism; BA + thyrotoxicosis. We assessed serum IgE, IgG levels, as wekk as IL-4/IFNγ, IL-4/IL-1, and IL-1/IL-6 ratios. Clinical exacerbations were observed more  frequently  in BA + hypothyroidism, as compared with BA patients. Remissions of BA were more prolonged  in BA patients,  than  in groups with BA + hypothyroidism, or BA + hyperthyroidism. Serum  IgE  levels were much  increased  in  the group with BA + hyperthyroidism. The  lowest IL-4/IFNγ ratio was revealed  in BA + hypothyroidism group versus BA and BA + hyperthyroidism groups. IL-4/IL-1 ratio was higher  in BA + hyperthyroidism group,  than  in BA and BA + hypothyroidism. Co-existence of hyperthyroidism with BA seems to enhance Th2 immune reactions dominating  in BA, whereas concomitant hypothyroidism may cause  a  reduction of Th2  immune  response.